Variable-height channels for microparticle characterization and display. Issue 14 (12th June 2020) - Mena, Sarah E.; de Beer, Martin P.; McCormick, Joseph; Habibi, Nahal; Lahann, Joerg; Burns, Mark A.
Abstract : A unique glass etching process creates variable height channels capable of separating particles or cells by size or deformability. Abstract : Characterizing and isolating microparticles of different sizes is often desirable and essential for biological analysis. In this work, we present a new and straightforward technique to fabricate variable-height glass microchannels for size-based passive trapping of microparticles. The fabrication technique uses controlled non-uniform exposure to an etchant solution to create channels of arbitrary height that vary in a predetermined way from the inlet to the outlet. Channels that vary from 1 μm to over 20 μm in height along a length of approximately 6 cm are shown to effectively and reproducibly separate particles by size including particles whose diameters differ by less than 100 nm when the standard deviation in size is less than 0.66 μm. Additionally, healthy red blood cells and red blood cells chemically modified with glutaraldehyde to reduce their deformability were introduced into different channels. The healthy cells can flow into shallower heights, while the less deformable ones are trapped at deeper heights. The macroscopic visualization of microparticle separation in these devices in addition to their ease of use, simple fabrication, low cost, and small size suggest their viability in the final detection step of many bead-based assay protocols.